Combined control mechanism of weathering and tectonics for basement granite of Qiongdongnan Basin, South China Sea - Junqiang WANG; Anqing CHEN; Lin HU; Mingcai HOU; Li YOU; Xiaohu HE; Haiyang CAO; Youyuan QUE; Fuhao XIONG; Wenbo WANG (Shiyou shiyan dizhi)
Reservoirs within buried hills in petroliferous basins represent a unique area of exploration. Recent discoveries in the Mesozoic granite buried hills of the Qiongdongnan Basin in the South China Sea show promising exploration prospects. Among these, the Songnan buried hill group in the basin's central part has rich drilling data, with several wells encountering basal granite reservoirs. Fracturing is crucial for reservoir formation in dense crystalline bedrock, but limited research on fracture characteristics and tectonic stress hampers basement buried hill reservoir exploration. This study examines multi-stage fracture development in the Songnan low uplift buried hill based on core observations, thin-section analysis, well logging, and seismic data from five wells. It analyzes cutting relationships, openness, morphology, orientation, and explores tectonic stresses forming two groups of fractures. Tectonic fractures and dissolution holes along them are the main reservoir spaces within the granite basement. They are categorized into northeast (NE) and northwest (NW) trending families. NE trending fractures result from the Paleo-Tethys Ocean closure during the Indosinian period, influencing NW trending fractures. Tectonic extrusion related to western Pacific Ocean subduction during the Yanshanian period contributes to both NE and NW trending fractures. High-density fractures in granite allow atmospheric and underwater seepage and dissolution, forming a three-layer weathered crust reservoir structure: sandstone conglomerate belts, weathering fracture zones, and inner fracture zones. The extensional detachment background during early Cenozoic rift basin formation activates pre-existing fracture systems, enhancing reservoir space through fracture relaxation.